Cyclosporin and renal graft histology. Issue 2 (February 1986) - d'Ardenne, A J; Dunnill, M S; Thompson, J F; McWhinnie, D; Wood, R F; Morris, P J
Abstract : The histology of renal allografts was compared in a series of 107 biopsies from patients receiving cyclosporin and 126 biopsies from patients receiving azathioprine and prednisolone. Patients receiving cyclosporin were converted to azathioprine and prednisolone 90 days after transplantation. Biopsies were taken routinely at 7, 21, 90, and 365 days, irrespective of clinical graft function and were examined "blind" by two independent observers. Interstitial haemorrhage was more common in patients treated with azathioprine and prednisolone corresponding with their poorer graft survival. Analysis of glomerular, tubular, vascular, and interstitial changes showed no other important differences between the two groups despite clinical evidence of reversible cyclosporin nephrotoxicity. Quantitation of interstitial fibrosis in 90 day biopsies showed it to be equal in prevalence after treatment with azathioprine and prednisolone and cyclosporin. It was preceded by diffuse interstitial cellular infiltration, a common finding in early biopsies. Diffuse cellular infiltrates were generally associated with higher serum creatinine concentrations and, if persistent, a poorer graft prognosis than focal infiltrates, but they were not always associated with renal dysfunction.